2020
DOI: 10.1002/lary.28540
|View full text |Cite
|
Sign up to set email alerts
|

Angular Vessels for Free‐Tissue Transfer in Head and Neck Reconstruction: Clinical Outcomes

Abstract: Objectives/Hypothesis: To evaluate the efficacy and reconstructive applications of angular vessel microvascular anastomosis in free-tissue transfer. Study Design: Retrospective cohort study. Methods: A study of patients treated from January 2010 to July 2017 was performed. Four hundred thirty patients undergoing free-tissue transfer at the Cleveland Clinic by a single reconstructive surgeon were reviewed. Patients in whom free-tissue transfer was performed using angular vessels were included. Patients in whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…An additional theoretical benefit provided by the minimal access incision relates to cosmesis, with a smaller and/or hidden incision providing patients with the potential for superior cosmetic outcomes. In our previous study examining the use of the angular vessel system for microvascular reconstruction, we demonstrated that the use of the nasolabial fold incision did not result in any facial asymmetry or permanent weakness 11 . However, further studies should be undertaken to more quantitatively assess the cosmetic outcomes of this approach.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…An additional theoretical benefit provided by the minimal access incision relates to cosmesis, with a smaller and/or hidden incision providing patients with the potential for superior cosmetic outcomes. In our previous study examining the use of the angular vessel system for microvascular reconstruction, we demonstrated that the use of the nasolabial fold incision did not result in any facial asymmetry or permanent weakness 11 . However, further studies should be undertaken to more quantitatively assess the cosmetic outcomes of this approach.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study examining the use of the angular vessel system for microvascular reconstruction, we demonstrated that the use of the nasolabial fold incision did not result in any facial asymmetry or permanent weakness. 11 However, further studies should be undertaken to more quantitatively assess the cosmetic outcomes of this approach. Finally, by avoiding traditional neck exploration in favor of a minimal access approach, there is the potential for a quicker recovery and more expedited discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal scapular artery has also been described as a viable recipient vessel during free flap reconstruction in a vessel-depleted neck [64] . Interposition vein grafts may be required to lengthen the venous and/or arterial pedicle despite appropriate pre-operative planning and intra-operative efforts with overall success rates around 85% [65] . Different vein grafts have been described in the literature, such as the external jugular, facial, and cephalic, but the saphenous vein is most commonly used.…”
Section: Recipient Vesselsmentioning
confidence: 99%
“…For example, the superficial temporal vessels are often easily reachable and have high success rates when there is minimal size mismatch. Unfortunately, prior surgeries such as craniotomies may damage them, making them non-viable recipient vessels [8] . The angular vessels are another recipient vessel option that has a high success rate and does not require as long a pedicle as cervical vessels [9] .…”
Section: Principles Of Skull Base Reconstructionmentioning
confidence: 99%